Comparison of Clinical Features and Outcomes of Appendectomy in Elderly vs. Non-Elderly: A Systematic Review and Meta-Analysis - Yuan, Jie; Chen, Qingfeng; Hong, Weicong; Yu, Lifeng; Li, Xuen (Frontiers in Surgery, 2022)
Background: To compare clinical and surgical outcomes of appendectomy among elderly and non-elderly subjects. Methods: A systematic search was conducted on PubMed, Scopus, and Google academic databases. Studies, observational in design, that compared peri-and post-operative outcomes of appendectomy, in patients with acute appendicitis, between elderly and non-elderly/younger subjects were considered for inclusion. Statistical analysis was performed using STATA software. Results: A total of 15 studies were included. Compared to non-elderly patients, those that were elderly had increased risk of complicated appendicitis [RR 2.38, 95% CI: 2.13, 2.66], peritonitis [RR 1.88, 95% CI: 1.36, 2.59] and conversion from laparoscopic to open appendectomy [RR 3.02, 95% CI: 2.31, 3.95]. The risk of overall post-operative complications [RR 2.59, 95% CI: 2.19, 3.06], intra-abdominal abscess [RR 1.84, 95% CI: 1.15, 2.96], wound infection [RR 3.80, 95% CI: 2.57, 5.61] and use of post-operative drainage [RR 1.14, 95% CI: 1.09, 1.19] was higher among the elderly. The risk of readmission (30-day) [RR 1.61, 95% CI: 1.16, 2.24] and mortality (30-day) [RR 12.48, 95% CI: 3.65, 42.7] was also higher among elderly. Conclusions: Findings suggest an increased risk of peri-and post-operative complications among elderly subjects undergoing appendectomy, compared to non-elderly subjects.